1984
DOI: 10.1126/science.6087454
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Line Expressing Vesicular Stomatitis Virus Glycoprotein Fuses at Low p H

Abstract: A stable cell line expressing a complementary DNA clone encoding the vesicular stomatitis virus glycoprotein fused and formed polykaryons at pH 5.5. The formation of polykaryons was dependent on the presence of glycoprotein anchored at the cell surface and could be prevented by incubation of cells with a monoclonal antibody to the glycoprotein. Fusion occurred at a pH 0.5 unit lower than that observed for cells infected with vesicular stomatitis virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 18 publications
1
98
0
Order By: Relevance
“…The mature, trimeric wt G protein catalyzes membrane fusion at pH values <6.2 (Florkiewicz and Rose, 1984;Riedel et al, 1984). Fusion activity is accompanied by a characteristic increase in the stability of the trimer (Doms et al, 1987).…”
Section: Conformation Of the Cytoplasmic Domain Mutantsmentioning
confidence: 99%
“…The mature, trimeric wt G protein catalyzes membrane fusion at pH values <6.2 (Florkiewicz and Rose, 1984;Riedel et al, 1984). Fusion activity is accompanied by a characteristic increase in the stability of the trimer (Doms et al, 1987).…”
Section: Conformation Of the Cytoplasmic Domain Mutantsmentioning
confidence: 99%
“…The acidification of these endosomes by an ATP-dependent proton pump is responsible for initiating the fusion of viral and cellular membranes (Eidelman et al, 1984;Florkiewicz and Rose, 1984). Recently, computer simulations of the structure of KFT25 and calculations of the hydropathicity and of the mean hydrophobic moment of the KFT25 peptide indicated that the peptide is composed of three distinct structural regions separated by Pro residues: an N-terminal hydrophobic a-helix (Lys-Pro region), a central hydrophilic globular structure (His-Pro region) and a slightly hydrophilic C-terminal 5-structure (Ser-Pro).…”
Section: Viruses and Viral Particlesmentioning
confidence: 99%
“…In VSV, which belongs to the family Rhabdoviridae, both viral attachment to the host cell as well as membrane fusion in the acidic environment of the endosomal compartment are mediated by the G protein (21)(22)(23). VSV recombinants have been used as vectors in vaccine studies (24,25) and VSV-G for pseudotyping of other enveloped viruses (26,27).…”
Section: Introductionmentioning
confidence: 99%